Where to go? Workers' Reasons to quit and Intra- versus Interindustry Job Mobility - Josse Delfgaauw (Tinbergen Institute, 2005)
This paper employs survey data on the reasons to quit of Dutch job changers who entered or left a public sector job in 2001. We show that workers' reasons to quit their public sector job influence their decision to stay in or leave their industry of employment. A bad experience with, for instance, pay, work pressure, or job duties makes a change in industry more likely. Likewise, many workers who quit out of dissatisfaction with pay or management leave the public sector altogether. Lastly, it is shown that workers' reasons to quit fully explain the differences in wage growth between intra- and interindustry job movers.
Keywords: J28; J31; J33; J45; J63; 330; Reasons to quit; Job mobility; Wages; Change in industry; Public sector workers; Arbeitsmobilität; Öffentlicher Sektor; Niederlande